Valoracion de la difenamida en el control de malezas en pinus caribaea var. caribaea - Betancourt, M.A.=700 1 Zuñiga, J.; Hernandez, D.
(Es, En)
Ilus., 4 ref.
Keywords: PINUS CARIBAEA; MALEZAS; ESCARDA; DIFENAMIDA; TOXICIDAD; CUBA